Near-infrared diffuse interstellar bands towards Her 36. Issue 3 (8th March 2019) - Rawlings, M G; Adamson, A J; Marshall, C C M; Sarre, P J
Abstract: Discovered almost a century ago, the diffuse interstellar bands (DIBs) still lack convincing and comprehensive identification. Hundreds of DIBs have now been observed in the near-ultraviolet (NUV), visible, and near-infrared (NIR). They are widely held to be molecular in origin, and modelling of their band profiles offers powerful constraints on molecular constants. Herschel 36, the illuminating star of the Lagoon Nebula, has been shown to possess unusually broad and asymmetric DIB profiles in the visible, and is also bright enough for NIR observation. We present here high-resolution spectroscopic observations targeting the two best-known NIR DIBs at 11 797.5 and 13 175 Å towards this object and a nearby comparison O-star, 9 Sgr, using the GNIRS instrument on Gemini North. We show a clear detection of the 13 175 Å DIB in both stars, and find (i) that it does not exhibit the unusual wing structure of some of the visual DIBs in Her 36 and (ii) that the depth of the band in the two objects is very similar, also contrary to the behaviour of the visual DIBs. We discuss the implications of these results for multiple DIB carrier candidates, and the location of their carriers along the observed lines of sight.